2011
DOI: 10.1108/17466661111190947
|View full text |Cite
|
Sign up to set email alerts
|

Fear is the key: keeping the balance between flexibility and control in a Dutch youth prison

Abstract: Fear is the key: keeping the balance between flexibility and control in a Dutch youth prison van der Helm, G.H.P.; Boekee, I.; Stams, G.J.J.M.; van der Laan, P.H. Published in:Journal of Children's Services DOI:10.1108/17466661111190947 Link to publicationCitation for published version (APA): van der Helm, P., Boekee, I., Stams, G. J., & van der Laan, P. (2011). Fear is the key: keeping the balance between flexibility and control in a Dutch youth prison. Journal of Children's Services, 6(4), 248-263. DOI: 10.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 75 publications
0
47
1
Order By: Relevance
“…Also, a closed living group climate has negative consequences for the safety of both sociotherapists and clients (Van der Helm et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Also, a closed living group climate has negative consequences for the safety of both sociotherapists and clients (Van der Helm et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Van der Helm et al . () provided an overview of climate research and found the same dimensions in a range of instruments measuring living group climate, namely, ‘support’, ‘growth’, ‘atmosphere’ and ‘repression’. These dimensions overlap with the basic psychological needs of clients (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…group climate, personality and aggression in incarcerated male youth Hostility among young inmates is associated with aggression and violence as a means to maintain control (Cheng, Tracy, & Henrich, 2010;Van der Helm, Boekee, Stams & van der Laan, in press). A repressive group climate has been shown to result in low self worth, anxiety, and aggression (Ostrowsky, 2010;Thomaes, 2007).…”
Section: Group Climate In Youth Prison and Aggressionmentioning
confidence: 99%
“…These aggressive situations can influence the occurrence of aggression in other patients as an effect of modeling (Fergusson & Horwood, 1996) as well as by the influence on neural mechanisms important for aggression (Fishbein & Sheppard, 2006;Nelson & Trainor, 2007). Moreover, aggressive incidents occurring in a psychiatric ward are shown to be associated with a decreased well-being of working staff, diminished professional behavior, an increased number of absences, and a higher workload (Di Martino, 2002;Estryn-Behar et al, 2008;Nijman, Palmstierna, Almvik, & Stolker, 2005;van der Helm, Boekee, Stams, & van der Laan, 2011). Furthermore, evidence exists for an association between inpatient aggression and a higher number of offenses after treatment (Cochran, Mears, Bales, & Stewart, 2014).…”
mentioning
confidence: 99%